2016
DOI: 10.1177/0268355515608992
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to and efficacy of different compression methods for treating chronic venous insufficiency in the elderly

Abstract: Objectives To investigate the adherence to and efficacy of different compression methods in elderly patients. Methods A retrospective review of compression therapy in 120 elderly patients (≥65 years) with chronic venous insufficiency was performed to study the initially preferred compression method, adherence to each method, and its efficacy. Results Initially, an oversize strong stocking (24%), an appropriate size moderate stocking (19%), and bandages (37%) were equally preferred. Adherence at 1 month was 69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“… 15 , 16 ) Further, elderly individuals prefer bandages because they are easy to use. 17 ) Our “no-intentional-stretch” technique rarely led to complications, such as ischemia and skin injury due to constriction, and ensured that IP and stiffness could be easily maintained and controlled. 8 ) This bandaging technique is expected to generate an IP of 40–45 mmHg and an SSI of 11–13 mmHg, and the values measured at the clinic were similar to these values.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 ) Further, elderly individuals prefer bandages because they are easy to use. 17 ) Our “no-intentional-stretch” technique rarely led to complications, such as ischemia and skin injury due to constriction, and ensured that IP and stiffness could be easily maintained and controlled. 8 ) This bandaging technique is expected to generate an IP of 40–45 mmHg and an SSI of 11–13 mmHg, and the values measured at the clinic were similar to these values.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in wearing CS, financial burden, discomfort of heat and tightness of stocking are responsible for low compliance of CS use in CVI patients. Suehiro et al indicated that 20% of CVI patients in all age groups refused compression treatment 23 ) . Raju et al reported that 63% of the patients failed to adapt to CS 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the duration of usage of CS 19 , 20 , 21 , 22 , 23 , 24 ) . It is known that venous hypertension increases after removing stockings.…”
Section: Discussionmentioning
confidence: 99%
“…Future RCTs assessing the efficacy of ECS should encourage compliance with ECS, via promoting physicians’ endorsement of ECS use, scheduling regular phone contact with the patient to reinforce compliance and improve reporting by the use of prospectively maintained diaries, which are the current “gold standard” for ECS compliance assessment 51 . However, beyond these measures, use of lighter ECS is probably one of the best and easiest ways to improve ECS compliance 52 …”
Section: Potential Limitations Of Published Rcts Assessing the Efficamentioning
confidence: 99%